2017
DOI: 10.1590/1678-7757-2016-0498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photodynamic therapy and non-thermal plasma on root canal filling: analysis of adhesion and sealer penetration

Abstract: Objective The aim of this study was to evaluate the effect of photodynamic therapy (PDT) and non-thermal plasma (NTP) on adhesion and sealer penetration in root canals.Material and Methods Sixty single-rooted premolars were used. The teeth were prepared using a crown-down technique. NaOCl and EDTA were used for irrigation and smear layer removal, respectively. The root canals were divided into three groups: control, PDT, and NTP. After treatments, the roots were filled using gutta-percha and either AH Plus (AH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 29 publications
2
27
1
Order By: Relevance
“…In PAD, the coronal and middle levels had significantly less smear layer and remaining debris than the apical level, this could be attributed to the presence of vapor lock may have hindered the action of the photosensitizing agent [21] . This finding was supported by other studies of Menezes et al [30] and Alonaizan et al [31] .…”
Section: Discussionsupporting
confidence: 89%
“…In PAD, the coronal and middle levels had significantly less smear layer and remaining debris than the apical level, this could be attributed to the presence of vapor lock may have hindered the action of the photosensitizing agent [21] . This finding was supported by other studies of Menezes et al [30] and Alonaizan et al [31] .…”
Section: Discussionsupporting
confidence: 89%
“…2. This thermal stability could be responsible for the biological activity of the cement surface to induce tooth integration, as reported by others 33,34 . Furthermore, it was evident that after the thermogravimetry test at 700°C, Zn particles and nHA were chemically compatible without interfering with the other's crystalline structure and stability 32 .…”
Section: Thermogravimetrysupporting
confidence: 57%
“…NTAP is being currently investigated as an antiseptic, and several studies have revealed the antibacterial effect both in vivo and in vitro [54]. In addition, the most obvious advantage that is accepted in this regard is that plasma achieves this effect without damaging human cells [55]. Recently, a clinical study indicated that singletime NTAP application together with non-surgical periodontal treatment provided additional clinical attachment level gains and better elimination of putative periodontopathogens and reduced their recolonization [41].…”
Section: Discussionmentioning
confidence: 99%